Career Maturity of Southwest Aceh State High School Students - Rahmiyati, Evi; Martunis, Martunis; Ummah, Izzatul (Universitas Pahlawan Tuanku Tambusai, 2025)
Career maturity has been positioned as an important indicator in assessing students' readiness to plan and make career decisions realistically. In this study, the picture of the level of career maturity of students has been analyzed through a descriptive quantitative approach. A total of 1,255 students from SMAN 2, SMAN 5, and SMAN 8 have been made into the population, and 302 students have been selected as samples using simple random sampling techniques. The instrument used is a career maturity scale with 35 statement items, which has been adapted from Savickas and Porfeli (2011). Based on the results of the analysis, it was found that 54% of students were categorized as having high career maturity, 27% moderate, 18% very high, and 1% low. When viewed from its aspects, attention to career has been shown to be high by 41% of students, curiosity by 46%, confidence by 43%, and consulting is in the very high category by 43% of students. Thus, it can be concluded that most students have shown good career readiness. The ability to choose a job, seek information, make decisions, and accept advice from others has been successfully shown as a form of maturity in their career.